The roles of librarians in copyright protection in Nigeria (2007)
This paper gives an overview of copyright issues in Nigeria with an emphasis on the librarians who are the custodians of most intellectual property. The paper dwells much on the librarians’ roles in the protection of their users’ rights as well as safeguarding the interest of creators. Such protection provides the necessary incentives for scientific, technological and intellectual creativity. Librarians need to pay close attention to the balance between promoting the users’ right as well as creators’ right. It is concluded that it is the responsibility of librarians to protect the copyright of authors. They have to discourage library users from infringing on copyright laws. The paper offers some suggestions that will reduce the infringement on copyright to the barest minimum.